Benefit Sharing as a Legal Protection Mechanism for Traditional Cultural Expressions: A Comparative Study of Indonesia and Malaysia under International Law - Susanti Susanti; Hari Sutra Disemadi; Elza Syarief (Journal of Judicial Review, 2026)
This study examines the benefit-sharing mechanism as an instrument for the protection of Traditional Cultural Expressions (TCEs) from the perspective of international law through a comparative analysis between Indonesia and Malaysia. TCEs constitute part of intangible cultural heritage that embodies economic, social, spiritual, and collective identity values of indigenous communities, yet they remain vulnerable to exploitation and misappropriation without fair distribution of benefits to their rightful custodians. This research aims to analyze the regulation of benefit sharing concerning TCEs in Indonesia and Malaysia, assess its conformity with principles of international law, and formulate an ideal regulatory model for TCE protection. The study employs normative legal research using statutory, conceptual, and comparative approaches. The legal materials consist of international instruments such as the Convention on Biological Diversity (CBD), the Nagoya Protocol, UNDRIP, and WIPO-IGC documents, as well as national regulations of Indonesia and Malaysia concerning cultural protection and communal intellectual property rights. The findings indicate that both Indonesia and Malaysia have provided normative recognition of TCEs; however, benefit-sharing arrangements remain partial and lack operational mechanisms. Indonesia emphasizes cultural preservation and recognition of indigenous communities, while Malaysia adopts a more pragmatic approach through specific regulatory initiatives and cultural commercialization. Nevertheless, both countries have not fully implemented the principles of Access and Benefit Sharing (ABS) and Free, Prior and Informed Consent (FPIC) as developed under international law. This study proposes a responsive law-based benefit-sharing model that positions indigenous communities as the primary legal subjects through meaningful participation, recognition of collective rights, transparency, and equitable and sustainable distribution of benefits.